Georeferencing and web publication of ancient mapping in geographic information systems: requirements for its evaluation and a case of study - Cascón Katchadourian, Jesús; Ruiz Rodríguez, Antonio; Quesada Román, Adolfo (Revista General de Información y Documentación, 2018)
With the arrival of new technologies the cartography is in fashion, the consumption of large-scale maps is a reality thanks to Google Maps and the GPS. These technologies have also brought their influence to ancient cartography, which is giving a new air with the modernization in the use and treatment of ancient maps. The processes that make this possible are, among others, digitization, georeferencing, and web publishing. These last two processes are carried out with the Geographic Information Systems (GIS). The objective of this article is to obtain a list of requirements that a GIS must fulfill in order to perform these processes satisfactorily for the user, as well as to test the free software QGIS with this listing. The purpose of this research is to provide valid knowledge and tools for librarians, archivists, and other information professionals who want to revitalize their cartographic collections.